2005
DOI: 10.1038/sj.leu.2403966
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of the MLL gene by activators of apoptosis is independent of topoisomerase II activity

Abstract: Exposure to topoisomerase II inhibitors is linked to the generation of leukemia involving translocations of the MLL gene, normally restricted to an 8.3 kbp tract, the breakpoint cluster region (BCR). Using an in vitro assay, apoptotic activators, including radiation and anti-CD95 antibody, trigger site-specific cleavage adjacent to exon 12 within the MLL BCR and promote translocation of the MLL gene in cells that can survive. To explore the mechanism of cleavage and rearrangement in more detail, the entire MLL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
35
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 25 publications
5
35
1
3
Order By: Relevance
“…Some translocations with leukemogenic potential are associated with recovery from initial apoptotic DNA fragmentation (20)(21)(22). The fact that ARTEMIS contributes to DNA fragmentation at early stages when apoptosis reversion is still possible suggests that ARTEMIS could play a role in such translocations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some translocations with leukemogenic potential are associated with recovery from initial apoptotic DNA fragmentation (20)(21)(22). The fact that ARTEMIS contributes to DNA fragmentation at early stages when apoptosis reversion is still possible suggests that ARTEMIS could play a role in such translocations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified cellular intermediates and reversible apoptotic states with potential genomic instability (19); as a result, propagation of some chromosome translocations, such as those involving the MLL gene in acute and therapy-related leukemias, may rely on recovery from initial apoptotic DNA fragmentation induced by genotoxic or nongenotoxic stimuli (20)(21)(22). In addition, it has been proposed that HMW DNA fragmentation corresponds to a nucleolytic cleavage at scaffold/ matrix attachment regions in chromosomes (23).…”
Section: Introductionmentioning
confidence: 99%
“…The use of epipodophyllotoxins in a chemotherapy regimen results in therapy-related acute leukaemia associated with translocations of the human MLL gene (Goto et al, 1994;Nasr et al, 1997). Subsequently, in vitro experiments demonstrated that certain cytotoxic drugs, topoisomerase II inhibitors, or CD95-mediated apoptosis are all able to induce DNA DSBs within SCII (Aplan et al, 1996;Stanulla et al, 1997;Felix et al, 1998;Andersen et al, 2001;Betti et al, 2001Betti et al, , 2005Sim and Liu, 2001;Libura et al, 2005). Further clues came from experiments that demonstrated DNase I hypersensitivity of SCII (Strissel et al, 1998) and elevated histone acetylation along MLL exons 11 and 14 (Khobta et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…18 and 19), and mapping of VP-16-induced DSBs to the bcr of the MLL gene has led to the suggestion of a direct link between these DSBs and MLL gene translocations (8,(12)(13)(14)(15)20). However, other studies have also pointed to the involvement of apoptotic nucleases in VP-16-induced DSBs within the bcr of the MLL gene (21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%